Effects of canagliflozin in patients with type 2 diabetes and chronic heart failure: a randomized trial (CANDLE). (25th November 2020) - Tanaka, A; Hisauchi, I; Taguchi, I; Sezai, A; Toyoda, S; Tomiyama, H; Sata, M; Ueda, S; Oyama, J; Kitakaze, M; Murohara, T; Node, K
Abstract: Background: Little is known about the impacts of sodium glucose co-transporter 2 inhibitors on cardiac functional parameters, such as natriuretic peptides, in type 2 diabetes (T2D) patients with concomitant chronic heart failure (CHF). Purpose: To compare the effect of canagliflozin with glimepiride, based on changes in N-terminal pro-brain natriuretic peptide (NT-proBNP), in that patient population. Methods: This trial was an investigator-initiated, multicenter, prospective, randomized, open-label, blinded-endpoint trial at 34 centers in Japan. Patients with T2D and clinically stable CHF excluding NYHA class IV, randomized to receive canagliflozin 100 mg or glimepiride (starting dose: 0.5 mg), were examined using the primary endpoint of non-inferiority of canagliflozin versus glimepiride, defined as a margin of 1.1 in the upper-limit of the 2-sided 95% confidence interval (95% CI) for the group ratio of percentage change in NT-proBNP at 24 weeks. Results: Data analysis of 233 patients (mean age 68.6±10.1 yrs; 75% male) showed mean left ventricular ejection fraction (LVEF) at randomization was 57.6±14.6%, with 71% of patients having a preserved LVEF (≥50%). The ratio of NT-proBNP percentage change was 0.48 (95% CI, −0.13 to 1.59, P=0.226), and therefore did not meet the prespecified non-inferiority margin. However, data stratified according to baseline NT-proBNP levels showed a trend that canagliflozin treatment reduced NT-proBNP levels to a greater extent than in subgroups with elevated levels of NT-proBNP (Figure A). Furthermore, NT-proBNP levels in the canagliflozin group did show a nonsignificant trend lower in the subgroup with preserved LVEF (Figure B), but not in the subgroup with reduced LVEF (Figure C). Additionally, the changes in the NYHA class were comparable between groups (P=0.061) in the overall cohort, whereas in the subgroup with a preserved LVEF canagliflozin caused a significant improvement in NYHA classes compared to that found for glimepiride treatment (P=0.027). Conclusions: This trial did not meet the predefined primary endpoint of changes in NT-proBNP levels, with 24 weeks of treatment with canagliflozin relative to glimepiride which together with other recent studies would question the value of continuing to monitor NT-proBNP levels after the initial diagnosis of heart failure. Nevertheless, in a subgroup with preserved LVEF, there was a non-significant trend for canagliflozin treatment to reduce NT-proBNP levels and improve symptoms even in stable HF patients. Further research is therefore warranted to determine whether patients with preserved LVEF, regardless of diabetes status, could potentially benefit from treatment with SGLT2 inhibitors. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Mitsubishi Tanabe Pharma Corporation